(untitled) (Research, Society and Development, 2026)
This study aimed to report and analyze, through a qualitative approach, the experiences lived during a supervised internship in Artistic Gymnastics and Rhythmic Gymnastics, focusing on the influence of the family environment on the behavior, motivation, and performance of young practitioners. This descriptive research, characterized as an experience report, was conducted between August and October 2024 in a gymnastics facility located in Manaus, Brazil, involving children and adolescents aged 5 to 15 years. Data were collected through field diaries, institutional reports, reflective records, and photographic documentation, and analyzed using content analysis. The findings showed that playful, progressive, and age-adapted pedagogical strategies enhanced engagement, participation, and learning. However, structural limitations such as lack of air conditioning and limited equipment affected performance and required methodological adaptations by professionals. Family participation was found to significantly influence attendance, motivation, emotional security, and long-term adherence to the sport. Family involvement presented a dual role: when balanced, it strengthened self-confidence and commitment; when excessive, it generated performance pressure. It is concluded that teacher mediation, guided family support, and adequate structural conditions are essential to promote healthy, meaningful, and formative sports experiences in youth gymnastics training.